Palliative Care in Children- A Holistic Dimension - Pauline Sharmila (Emerging Trends in Disease and Health Research Vol. 9, 2022)
Palliative care is a holistic care concept for people suffering from chronic illness or terminal illness. The care is given right from the time of the first diagnosis of the illness, which instils lots of fear and anxiety in the minds of the parents of the child diagnosed with a serious illness. The main aim is to give multidisciplinary care and alleviate the suffering and render quality of life. Not only the child who is suffering with the disease is taken care of, but the entire family is handled with care and concern. Nursing care and the ethical issues concerned with terminal illness is discussed and the models of holistic care and PCT (Palliative care team) are also described here.